$\begin{array}{1 1}(A)\;\large\frac{2}{15}\\(B)\;\large\frac{3}{15}\\(C)\;\large\frac{4}{15}\\(D)\;\text{None of these}\end{array} $

- $P(A\cup B)=P(A)+P(B)-P(A\cap B)$

Step 1:

Given 60 students

n(NCC)=30

n(NSS)=32

$n(NCC\cap NSS)=24$

$\therefore P(NCC)=\large\frac{30}{60}$

$P(NSS)=\large\frac{32}{60}$

$P(NCC \cap NSS)=\large\frac{24}{60}$

Step 2:

The student has opted NSS but not NCC

$\therefore$ P(The student has opted NSS but not NCC)

$\Rightarrow P(NSS)-P(NCC \cap NSS)$

$\Rightarrow \large\frac{32}{60}-\frac{24}{60}$

$\Rightarrow \large\frac{8}{60}$

$\Rightarrow \large\frac{2}{15}$

Hence (A) is the correct answer.

Ask Question

Tag:MathPhyChemBioOther

Take Test

...